2019
DOI: 10.1016/j.jsurg.2018.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of the Communication Skills Attitude Scale (CSAS) to Surgical Residents in China

Abstract: The data suggest that the Chinese version of CSAS developed to assess surgery residents are feasible and provide valid and reliable evidence. Further research is necessary to explore and understand attitudes toward communication skills of surgical residents in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Participants evaluated their agreement with each item on a 5-point Likert scale from 1 (strongly disagree) to 5 (strongly agree). Two subscales were calculated, a positive attitude scale (PAS) and a negative attitude scale (NAS) as done before [ 37 ]. The PAS shows a maximum score of 70 and a minimum score of 14, whereas the NAS ranges between 60 and 12.…”
Section: Methodsmentioning
confidence: 99%
“…Participants evaluated their agreement with each item on a 5-point Likert scale from 1 (strongly disagree) to 5 (strongly agree). Two subscales were calculated, a positive attitude scale (PAS) and a negative attitude scale (NAS) as done before [ 37 ]. The PAS shows a maximum score of 70 and a minimum score of 14, whereas the NAS ranges between 60 and 12.…”
Section: Methodsmentioning
confidence: 99%
“…The CSAS, with good reliability and validity, is currently the most widely used tool for evaluating medical students' attitudes towards CS learning. Many countries and regions (such as Norway, South Korea, the United States and China) used PAS and NAS to evaluate the learning attitude of medical students' communication skills, founding that there are differences formed by corresponding national demographics [ 10 13 ]. Previous tudies have shown that gender affects medical students’ attitudes toward CS learning, manifested as higher PAS scores and lower NAS scores for female students than male students [ 9 , 13 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many countries and regions (such as Norway, South Korea, the United States and China) used PAS and NAS to evaluate the learning attitude of medical students' communication skills, founding that there are differences formed by corresponding national demographics [ 10 13 ]. Previous tudies have shown that gender affects medical students’ attitudes toward CS learning, manifested as higher PAS scores and lower NAS scores for female students than male students [ 9 , 13 , 26 ]. However, in the two teaching modes in this study, there was no gender difference in the learning attitude toward CS, which may be related to the small sample size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants evaluated their agreement with each item on a ve-point Likert scale from 1 (strongly disagree) to 5 (strongly agree). Two subscales were calculated, a positive attitude scale (PAS) and a negative attitude scale (NAS) as done before [34]. The PAS shows a maximum score of 70 and a minimum score of 14, whereas the NAS ranges between 60 and 12.…”
Section: Measurementsmentioning
confidence: 99%